MENINGKATKAN FUNGSI LEMBAGA LOKAL UNTUK PENGEMBANGAN DESA MANDIRI PANGAN - Dumasari Dumasari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2008)
Problem of food insecurity either in macro level (national) and also micro level (household/individual) always represent problems fundamental to development of quality of human resources being so that make proper and important to continue to be paid attention seriously. At this article, one of the solution alternative placed forward to solve problem food insecurity namely by improving local institute function to develop self supporting countryside of food. This theme is studied from various dimension with coverage of analyse which do not be quit of existence of farmers as majority citizen which living in rural area.